Adhesion behaviors of water droplets on bioinspired superhydrophobic surfaces. (1st July 2022) - Xu, Peng; Zhang, Yurong; Li, Lijun; Lin, Zhen; Zhu, Bo; Chen, Wenhui; Li, Gang; Liu, Hongtao; Xiao, Kangjian; Xiong, Yunhe; Yang, Sixing; Lei, Yifeng; et al.
Abstract: The adhesion behaviors of droplets on surfaces are attracting increasing attention due to their various applications. Many bioinspired superhydrophobic surfaces with different adhesion states have been constructed in order to mimic the functions of natural surfaces such as a lotus leaf, a rose petal, butterfly wings, etc. In this review, we first present a brief introduction to the fundamental theories of the adhesion behaviors of droplets on various surfaces, including low adhesion, high adhesion and anisotropic adhesion states. Then, different techniques to characterize droplet adhesion on these surfaces, including the rotating disk technique, the atomic force microscope cantilever technique, and capillary sensor-based techniques, are described. Wetting behaviors, and the switching between different adhesion states on bioinspired surfaces, are also summarized and discussed. Subsequently, the diverse applications of bioinspired surfaces, including water collection, liquid transport, drag reduction, and oil/water separation, are discussed. Finally, the challenges of using liquid adhesion behaviors on various surfaces, and future applications of these surfaces, are discussed.